If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + (6n + 9N) = 0 Reorder the terms: 8 + (9N + 6n) = 0 Remove parenthesis around (9N + 6n) 8 + 9N + 6n = 0 Solving 8 + 9N + 6n = 0 Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + 9N + -8 + 6n = 0 + -8 Reorder the terms: 8 + -8 + 9N + 6n = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 9N + 6n = 0 + -8 9N + 6n = 0 + -8 Combine like terms: 0 + -8 = -8 9N + 6n = -8 Add '-6n' to each side of the equation. 9N + 6n + -6n = -8 + -6n Combine like terms: 6n + -6n = 0 9N + 0 = -8 + -6n 9N = -8 + -6n Divide each side by '9'. N = -0.8888888889 + -0.6666666667n Simplifying N = -0.8888888889 + -0.6666666667n
| 2(x+4)=4x+34 | | 42x-30x^2=0 | | 4(3x-7)+8=2x+10 | | 10x-5+4=4 | | 4*(1/2+x)=3 | | 0.075(p+2000)=0.08p+0.03(2000) | | 8=-(x+4) | | 2x-3=42-7x | | 5+3r=5r-14 | | 1+1/2= | | 6h=-30 | | (x+5)(x+5)=0 | | 7(7p-4)=-175 | | 2x-3=32-7x | | 160+x= | | 0.1(50)=0.2(60+x)-0.4x | | x^3-3x^2-45x+94=0 | | 0.3x-0.5(5)=0.2 | | -40=-5d | | 11(x+3)=-2(2x+6) | | -6-3=3-6y | | 2x+3=10+x | | -r+(3r^2+1)r=4 | | 5x-12x-7=8 | | -8=f/5 | | 38-4x=6(x+8) | | -3=k+3 | | (2t^2+7t-6)-(3t^2-11t-9)=0 | | 23=3+37t-16t^2 | | -8=2+3m-1 | | 5(x+3)-(2x-1)=3 | | 0.35x+.05(12-x)=.10(-48) |